2018
DOI: 10.1186/s12014-018-9182-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycan analysis of colorectal cancer samples reveals stage-dependent changes in CEA glycosylation patterns

Abstract: BackgroundCarcinoembryonic antigen (CEA) is a glycoprotein associated with colorectal cancer (CRC). While the functions of its gene and protein have been fully characterized, its post-translational modifications in the context of CRC development remain undefined.MethodsTo show the correlation between the different stages of CRC development and changes in the glycosylation patterns of CEA, we analyzed CEA in tumor tissues (CEA-T) and paired tumor-adjacent normal tissues (CEA-A) from 53 colorectal cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 48 publications
4
34
0
2
Order By: Relevance
“…Galactosylation was found to be decreased in lung cancer tissues and on the tumor-associated human carcinoma antigen (CEA) in CRC [19,62]. Zhao et al, hypothesized that the down-regulated galactosylation on CEA in tumor may be correlated with CRC immune response [19]. The stroma is largely orchestrated by inflammatory and immune cells, so the increased level of galactosylation in our study may be correlated to the inflammatory/immune response against cancer cells.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Galactosylation was found to be decreased in lung cancer tissues and on the tumor-associated human carcinoma antigen (CEA) in CRC [19,62]. Zhao et al, hypothesized that the down-regulated galactosylation on CEA in tumor may be correlated with CRC immune response [19]. The stroma is largely orchestrated by inflammatory and immune cells, so the increased level of galactosylation in our study may be correlated to the inflammatory/immune response against cancer cells.…”
Section: Discussionsupporting
confidence: 52%
“…The interface stroma of the group with longer survival was characterized by an increase of galactosylation per antenna in the diantennary complex-types glycans. Galactosylation was found to be decreased in lung cancer tissues and on the tumor-associated human carcinoma antigen (CEA) in CRC [19,62]. Zhao et al, hypothesized that the down-regulated galactosylation on CEA in tumor may be correlated with CRC immune response [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CEA gene was recently classified as an immunoglobulin gene super family member . One recent research showed CEA was a glycoprotein associated with colorectal cancer (CRC) and the changing CEA glycosylation patterns and their role in the development of CRC highlight the importance of glycan variants on CEA for early clinical detection and staging of CRC …”
Section: Discussionmentioning
confidence: 99%
“…24 One recent research showed CEA was a glycoprotein associated with colorectal cancer (CRC) and the changing CEA glycosylation patterns and their role in the development of CRC highlight the importance of glycan variants on CEA for early clinical detection and staging of CRC. 25 CEA is a widely used tumor marker globally and can not only be detected in the blood of CRC patients but also in the tumor tissue. 26 The CEA gene and antibody expressions in tumor tissues have already been studied; however, studies on s-CEA and its prognostic value in CRC, locally and internationally, are relatively limited and are not comprehensive.…”
Section: Discussionmentioning
confidence: 99%